The Impact of Monsoon Flood Phenomenon on Tourism Sector in Kelantan, Malaysia: A Review - Nurashikin Sungip, Fauzi; Khairul Amri Kamarudin, Mohd; Hafiz Md Saad, Muhammad; Abd Wahab, Noorjima; Puad Mat Som, Ahmad; Umar, Roslan; Ing Hoe, Loh; Hakparn, Surachate; Lertbunchardwong, Kanittha; Potikengrith, Tepvisit; Harith, Hazamri (International Journal of Engineering and Technology, 2018)
The northeast monsoon flood phenomenon is a natural disaster especially around East Peninsular Malaysia such as Kelantan. The main objective of this study is to identify the impact of the northeastern monsoon flood of Malaysia on the tourism sector. The climatology factors for tourism sector especially for the coastal zone tourism segment. Large floods as in 2014 have seen a lot of destroying local areas. Both the government and the non-government should formulate strategies to address the flood issue as a process of improvement for the future. Flood effects such as damage to building infrastructure, coastal beauty, facilities, interrupted services and tourist attractions. The findings show that floods that are among the most frequent climate change in all countries in Malaysia. However, the impact of this disaster will not only affect flood-damaged areas but also indirectly affect the growth of the tourism sector as it requires a reconstruction process. The study was conducted to illustrate the impact of the flood disaster that has affected the tourism sector.Â Â